Resilience regulation: An incentive scheme for regulated electricity network operators to improve resilience - Gert Brunekreeft; Marius Buchmann; Martin Palovic; Anna Pechan (Constructor University Bremen, Bremen Energy Research (BER), 2023)
This paper presents an approach for resilience incentives in the regulation of electricity network operators. Resilience is the ability of the power system to deal quickly and efficiently with large-scale and long-lasting power interruptions. It comprises two related aspects: minimizing the damage caused by an outage and increasing the robustness of the system. The resilience regulation proposed in this paper contains two complementary parts. First, a resilience incentive mechanism, which aims at internalizing external effects of resilience improvement. This part relies on so-called duration-dependent consumer damage functions (CDFs). Second, a forward-looking budget approach with a sharing factor to strengthen incentives for resilience expenses within regulatory constraints.
Keywords: K23; L5; L94; 330; resilience; electricity; network; regulation